Macroeconomic Determinants of Household Consumption Expenditure in Ghana: A Multivariate Cointegration Approach - Bonsu, Christiana Osei; Muzindutsi, Paul-Francois (International Journal of Economics and Financial Issues, 2017)
Household consumption is generally considered to be the final purpose of economic activity, and the level of consumption per person is often viewed as a central measure of an economy's productive success. Thus, consumption is among the key determinants of well-being of citizens at the global level. This study used a multivariate cointegration approach to analyse the macroeconomic determinants of household consumption expenditure in Ghana. The sample period consists of annual time series from 1961 to 2013. The vector autoregressive (VAR) model and Johansen cointegration approach were used to capture the short- and long-run relationships between selected macroeconomic variables and the household consumption in Ghana. The cointegration analysis revealed a significant long-run relationship between real household consumption and selected macroeconomic variables with a marginal propensity to consume of 0.7971. Granger causality, impulse response analysis and variance decomposition showed that, in the short run, household consumption is only affected by changes in price levels, while it has a significant effect on the real exchange rate and real economic growth. Findings reported in this study are helpful in understanding the macroeconomic role of household consumption expenditure in the Ghanaian economy. Keywords: Cointegration, Ghana, household consumption, macroeconomic variables, VAR JEL Classifications: E21, C30